Occupation preference values in doped CmIm' multinaries from EXAFS and FTIR correlative analysis - Robouch, B.V.; Marcelli, A.; Robouch, P.; Kisiel, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We discuss which x-ray absorption fine structure (EXAFS) data of binary doped CmIm' compound structures can be unfolded to determine elemental bond distances and the deviations from random configurations due to site preference occupations (SOPs). SOP-deviation estimations can be further confirmed by independent Fouriertransform infrared (FTIR) data analysis. The limits and restrictions of our model are presented and discussed.